Metallic Nickel Hydroxide Nanosheets Give Superior Electrocatalytic Oxidation of Urea for Fuel Cells. (30th August 2016) - Zhu, Xiaojiao; Dou, Xinyu; Dai, Jun; An, Xingda; Guo, Yuqiao; Zhang, Lidong; Tao, Shi; Zhao, Jiyin; Chu, Wangsheng; Zeng, Xiao Cheng; Wu, Changzheng; Xie, Yi
Abstract: The direct urea fuel cell (DUFC) is an important but challenging renewable energy production technology, it offers great promise for energy‐sustainable developments and mitigating water contamination. However, DUFCs still suffer from the sluggish kinetics of the urea oxidation reaction (UOR) owing to a 6 e − transfer process, which poses a severe hindrance to their practical use. Herein, taking β‐Ni(OH)2 nanosheets as the proof‐of‐concept study, we demonstrated a surface‐chemistry strategy to achieve metallic Ni(OH)2 nanosheets by engineering their electronic structure, representing a first metallic configuration of transition‐metal hydroxides. Surface sulfur incorporation successfully brings synergetic effects of more exposed active sites, good wetting behavior, and effective electron transport, giving rise to greatly enhanced performance for UOR. Metallic nanosheets exhibited a much higher current density, smaller onset potential and stronger durability.